2009
DOI: 10.1007/s10528-009-9246-2
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population

Abstract: Polymorphisms in DNA repair genes are good candidates for modifying cancer risk. ERCC2/XPD, a gene involved in nucleotide excision repair and basal transcription, may influence individual DNA repair capacity, particularly of bulky adducts. This is implicated in cancer susceptibility. To detect the association between ERCC2/XPD Arg156Arg and susceptibility to breast cancer in a Chinese population, we conducted a hospital-based case-control study consisting of 129 patients with breast cancer and 205 controls mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…There were more subjects with family history of cancer (defined as first or second degree relatives) among cases (11.9%) than among controls (0.9%) (P b 0.001) ( Table 1). The minor allele frequencies were 0.10 for XRCC1 Pro206Pro and 0.48 for ERCC2 Arg156Arg among controls, respectively, and thus similar to our previous reports (Table 2) (Yin et al, 2007(Yin et al, , 2008(Yin et al, , 2009a. The genotype distributions of XRCC1 Pro206Pro and ERCC2 Arg156Arg among healthy controls were consistent with those predicted from Hardy-Weinberg equilibrium (P = 0.80 and P = 0.87, respectively) ( Table 2).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…There were more subjects with family history of cancer (defined as first or second degree relatives) among cases (11.9%) than among controls (0.9%) (P b 0.001) ( Table 1). The minor allele frequencies were 0.10 for XRCC1 Pro206Pro and 0.48 for ERCC2 Arg156Arg among controls, respectively, and thus similar to our previous reports (Table 2) (Yin et al, 2007(Yin et al, , 2008(Yin et al, , 2009a. The genotype distributions of XRCC1 Pro206Pro and ERCC2 Arg156Arg among healthy controls were consistent with those predicted from Hardy-Weinberg equilibrium (P = 0.80 and P = 0.87, respectively) ( Table 2).…”
Section: Resultssupporting
confidence: 89%
“…Genotypes were AA (432 bp), AG (432, 344 and 88 bp) and GG (344 and 88 bp). For ERCC2 Arg156Arg, the genotyping data were published previously (Yin et al, 2009a).…”
Section: Laboratory Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently with their finding, we also found that the minor A allele of ERCC2 rs238406 was associated with high BPDE-DNA adduct levels and low DNA repair capacity. These results were also in line with three studies on ERCC2 rs238406 polymorphisms based on the Chinese population [48][50]. However, Lovatt et al [51] reported that those genotypes were associated with a low risk of skin cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, an accompanying higher expression of another gene may confer increased cancer risk. Previous studies demonstrated that XPD codon 156 polymorphisms were associated with lung (20), bladder (21) and breast cancer (22) in Chinese populations. To the best of our knowledge, the present study was the first to demonstrate that the silent polymorphisms of XPD156 affect the risk of PCa.…”
Section: Discussionmentioning
confidence: 98%